GDPR and the processing of personal data relating to criminal convictions and offences for research purposes (Rivista di Studi e Ricerche sulla criminalità organizzata, 2019)
Under the General Data Protection Regulation (UE) 2016/679, the processing of personal data relating to criminal convictions and offences is lawful only if authorised by Member State law. In Italy, a ministerial decree will dictate which kinds of processing are allowed, apart from those already authorised by the law. This article argues that such a decree should authorise the processing of court-case files’ copies for the purpose of documentation, study and research.Keywords: General Data Protection Regulation, GDPR, personal data relating to criminal convictions and offences, freedom of expression